Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
g(x) = x² - 4 is already in form of a variable, I.e., x
g(4x) takes another variable, I.e., 4x
Same as before, 4x takes over x:
=> g(4x) = (4x)² - 4
- (ax)² = a²x², where a is some arbitrary constant.
Answer:
=> g(4x) = 16x² - 4
OR
=> g(4x) = 4{4x² - 1}
[tex]\large{\rm{\underline{\underline{Answer:}}}}[/tex]
- Given g(x) = x² - 4 which is function of x and changes with the value of x
Now we have g(4x). This means, we have to replace x by 4x and correspondence to this, the equation will change. I.e.
⇛ g(4x) = (4x)² - 4
⇛ g(4x) = 16x² - 4 / 4(4x² - 1) [answer]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.